Environmental Effects of Sand and Gravel Mining on Land and Soil in Luku, North Central Nigeria (Global Journal of Science Frontier Research, 2014)
The increase in the demand for sand and gravel for construction and other purposes such as flood control has placed immense pressure on the environment where sand and gravel resources occur. This study was carried out to determine the environmental effects of sand and gravel mining in Luku, North central Nigeria, using field observations and laboratory analysis of soil samples. Field work was carried out in the area to determine the physical environmental effects of mining while soil samples were analysed at the National Geo-science Research Laboratory (NGRL), of Nigerian Geological Survey Agency (NGSA), Kaduna for trace elements using X-Ray Fluorescence (XRF) method. Result of the field observations shows that destruction of landscape, reduction of farm and grazing land, collapsing river banks, deforestation and water pollution are the environmental effects that result due to sand and gravel mining in the area. Result of the chemical analysis shows that average concentrations of Pb, As, Cu, Ni, Cd, Hg, Ag and Zr are 47.8, 4.17, 50.9, 32.7, 2.48, 0.1, 0.8 and 496.1ppm respectively. These concentrations are higher than the average standard concentrations of these elements found in the upper continental crust. These higher concentrations may have very negative effects on plants and animals in the area and cause diseases such as brain and kidney damage, lung irritation, cadiac abnormality and event death to plants and animals.